2014
DOI: 10.1055/s-0034-1378583
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Free Hunsdiecker Reaction of Electron-Rich Arenecarboxylic Acids and Aryl Aldehydes in Water

Abstract: An I 2 O 5 -mediated decarboxylative and decarbonylative bromination/iodination of electron-rich arenecarboxylic acids and aryl aldehydes by using KBr/KI as the halogen source in water has been developed. This scalable, low-cost, and transition-metal-free halogenation allows convenient access to aryl bromide and iodide under mild conditions. Direct decarboxylative halogenation of carboxylic acid represents one of the most useful strategies for the preparation of halides in synthetic organic chemistry, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…disclosed an I 2 O 5 −KX (X=Br, I) combination, which permits halogenations in water (Scheme 9). [171] Another effective system consists of sodium persulfate (Na 2 S 2 O 8 ) as the oxidant and N ‐halosuccinimide (NXS) (X=Cl, Br, I) as halogen sources [172] . Although both protocols proceed under mild condition, they are limited to benzoic acids bearing at least two electron‐donating groups (−OR, −NH 2 ), and lead to dihaloarenes as byproducts as a result of an additional electrophilic aromatic substitution (S E Ar) in the activated aromatic ring (Scheme 9B).…”
Section: Decarboxylative C‐halogen Bond Formationmentioning
confidence: 99%
“…disclosed an I 2 O 5 −KX (X=Br, I) combination, which permits halogenations in water (Scheme 9). [171] Another effective system consists of sodium persulfate (Na 2 S 2 O 8 ) as the oxidant and N ‐halosuccinimide (NXS) (X=Cl, Br, I) as halogen sources [172] . Although both protocols proceed under mild condition, they are limited to benzoic acids bearing at least two electron‐donating groups (−OR, −NH 2 ), and lead to dihaloarenes as byproducts as a result of an additional electrophilic aromatic substitution (S E Ar) in the activated aromatic ring (Scheme 9B).…”
Section: Decarboxylative C‐halogen Bond Formationmentioning
confidence: 99%
“…Liu et al demonstrated the applicability of the iodine pentoxide-KX system for the preparation of mono-, di-, and even trihalides in the presence of various methoxy or amino-groups (Scheme ). However, additional electron-withdrawing groups, such as Cl and Br, reduced the product yield or made the reaction impossible, as was observed for 2,6-dimethoxy-3-bromobenzoic acid ( 423 ).…”
Section: Additional Methods For the Halodecarboxylation Of Aromatic C...mentioning
confidence: 99%
“…[ 22 , 23 , 24 ] However, current reactions still exhibit several drawbacks: they either require preactivation of the carboxylic acid, [23b] stoichiometric amounts of transition metal,[ 23c , 23d ] or a tailor‐made Ir‐photocatalyst for the installation of the carbon−iodine bond. [ 23b , 23e ] In addition, several reports show limited substrate scope,[ 23f , 23g ] or afford the desired aryl iodides in only modest yields. [23h] Larrosa et al.…”
Section: Introductionmentioning
confidence: 99%